Multi-hyperbolic tangent fuzzy c-means algorithm with spatial information for MRI segmentation. (2016) - Venu, Nookala; Anuradha, B.
This paper proposes a novel image segmentation using Multi-Hyperbolic Tangent Fuzzy C-Means (HTFCM) algorithm, with spatial information for medical image segmentation. The proposed method uses two hyperbolic tangent functions with the spatial information of neighbouring pixels for clustering of images. The performance of the proposed algorithm is tested on OASIS-MRI image data set. The performance is tested in terms of score, number of iterations (NI) and execution time (TM) under different Gaussian and salt & pepper noises on OASIS-MRI data set. The results after investigating the proposed method show a significant improvement as compared to other existing methods in terms of score, NI and TM under different Gaussian and salt & pepper noises on OASIS-MRI data set.